Trade Effects of Currency Unions : Do Economic Dissimilarities Matter? - Albertin, Giorgia (IMF Working Papers; Working Paper, 2008)
This paper provides a general equilibrium analysis of the trade effects of the formation of a currency union, and of its subsequent enlargement to include an economically dissimilar country. Furthermore, it investigates how economic dissimilarities among countries affect the magnitude of the trade effects fostered by a common currency. We show that sharing a common currency enhances the volume of bilateral trade among countries. However, the more economically dissimilar is an accession country, compared to the original members of a currency union, the smaller are the gains in trade that would follow the enlargement of a currency union.